The Skinscape: Reflections on the Dermalogical Turn. (June 2018) - Howes, David
This article theorizes the dermalogical turn – heralded by the publication of this special issue – from a sensory studies perspective. Sensory studies involves a cultural approach to the study of the senses and a sensory approach to the study of culture. The skin is both an object and means of perception. Understandings of the skin and of touch vary across cultures: the skin may be seen as social rather than individual, as porous instead of an envelope, and as knowledgeable or sentient in its own right rather than subservient to the eye or brain (i.e. cognition). These contrasting understandings have important implications for practice. Haptic Field, a performative sensory environment designed by Chris Salter, which enables the visitor to try on a second skin, is discussed as a means of shaking up conventional Western understandings of the skin and of touch, and facilitating the communication of skin knowledge across cultures.